2020
DOI: 10.12659/msm.921719
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Laminectomy with Instrumented Fixation in Treating Thoracolumbar Intradural Extramedullary Schwannomas: A Comparative Study

Abstract: Departmental sources Background:This study investigated the clinical effect of laminectomy plus pedicle screw fixation in treating thoracolumbar intradural extramedullary schwannomas. Material/Methods:Between October 2011 and May 2017, 57 patients undergoing resection of thoracolumbar schwannomas were retrospectively identified and included in the study. Based on the surgical procedures used, all participants were assigned to either the laminectomy-only group (n=33) or the combination group (laminectomy plus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…BIPAP therapy, as an important means for the treatment of COPD complicated with respiratory failure, is widely used in clinical practice at home and abroad. 15 According to this study, the improvement of pulmonary respiratory function and blood gas analysis related indicators in the observation group was significantly better than that in the control group after treatment, which was similar to the results of Wang L et al 16 , suggesting that BIPAP can effectively improve the lung function of patients with COPD complicated with anxiety and depression.…”
Section: Discussionsupporting
confidence: 83%
“…BIPAP therapy, as an important means for the treatment of COPD complicated with respiratory failure, is widely used in clinical practice at home and abroad. 15 According to this study, the improvement of pulmonary respiratory function and blood gas analysis related indicators in the observation group was significantly better than that in the control group after treatment, which was similar to the results of Wang L et al 16 , suggesting that BIPAP can effectively improve the lung function of patients with COPD complicated with anxiety and depression.…”
Section: Discussionsupporting
confidence: 83%
“…Due to the large extent of the lesion and the involvement of intervertebral foramen, our patient underwent posterior total laminectomy, took the screw-rod system fixation and partly bone grafting. The internal fixation not only ensured complete tumor removal, but also stabilized the spine and promoted bone graft fusion [27,28]. Chemotherapy regimens are identical for EES and ESB, including vincristine, doxorubicin, and cyclophosphamide alternating with ifosfamide and etoposide [1].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown positive outcomes for IDEM tumours regardless of IONM use, achieving gross total resection (GTR) rates of >90%, postoperative complication rates of <20%, and >80% of patients having either stable or improved neurological function at follow-up. [26][27][28][29] Even when IONM alarms have sounded intraoperatively, suggesting immediate deficit and the need to use standard measures to improve microvascular perfusion as described above, studies have found improved patient outcomes with IONM usage. 30 However, a few studies report permanent new neurological deficits as a result of surgery, regardless of IONM use.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, a few studies report permanent new neurological deficits as a result of surgery, regardless of IONM use. [26][27][28][29]31,32 The good overall neurological outcomes in surgery for IDEM tumours might have been partially responsible for a high prevalence of anterolateral lesions in the non-IONM group, since patients were not randomised, the use of IONM instead being determined by surgical team preference. Furthermore, in a significant number of patients (related with preoperative ASIA score), MEPs, SSEPs or both could not be recorded.…”
Section: Discussionmentioning
confidence: 99%